2019
DOI: 10.3390/ijms20030674
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Headgroup Charge and Acyl Chain Composition Modulate Closure of Bacterial β-Barrel Channels

Abstract: The outer membrane of Gram-negative bacteria contains β-barrel proteins that form high-conducting ion channels providing a path for hydrophilic molecules, including antibiotics. Traditionally, these proteins have been considered to exist only in an open state so that regulation of outer membrane permeability was accomplished via protein expression. However, electrophysiological recordings show that β-barrel channels respond to transmembrane voltages by characteristically switching from a high-conducting, open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We note that a wide variety of structurally dissimilar β-barrel channels are observed to gate at sufficiently high potentials. , Many of these occur as trimers, or have small barrel diameters, both of which provide additional mechanical stability relative to VDAC. It is thus suggestive that VDAC is the most voltage-sensitive of these channels and has the most β-barrel flexibility.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We note that a wide variety of structurally dissimilar β-barrel channels are observed to gate at sufficiently high potentials. , Many of these occur as trimers, or have small barrel diameters, both of which provide additional mechanical stability relative to VDAC. It is thus suggestive that VDAC is the most voltage-sensitive of these channels and has the most β-barrel flexibility.…”
Section: Discussionmentioning
confidence: 96%
“…Voltage gating is a common property of β-barrel channels and has been observed in bacterial outer membrane porins 15 well as in the anthrax, 16 aerolysin, 17 and α-hemolysin 18 toxins. In contrast to these channels, where gating is observed at transmembrane potentials of 70 mV or higher, the sensitivity of VDAC gating to voltage is extraordinary, occurring at 30 mV or lower.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another property often considered to characterize the response of biological channels to changes in membrane polarization, a key cellular and intracellular mechanism, is the voltage-induced gating. It refers to conformational transitions between fully conductive (open) states and other (closed) states where transport of ions or other metabolites is partially or totally inhibited 69 . Although PI NP does not show voltage-induced closures and a direct comparison is not possible, it is noteworthy that in OmpF porin, voltage gating also exhibits a biphasic scaling with concentration (Figure S4).…”
Section: Biphasic Concentration Patternsmentioning
confidence: 99%
“…[16] Negatively charged lipids observed to bind differentially to the outer membrane porin, OmpF, by native MS were also found to affect OmpF channel opening/closure times. [17,18] Cardiolipin (CDL) was observed to stabilize and facilitate assembly of the NhaA Na + /H + antiporter. [19,20] In addition, pairing MS observations with functional assays has shown that PG binding increases Erwinia ligandgated ion channel (ELIC) function,[21••] PIP2 enhances coupling of Class A G protein-coupled receptors with heterotrimeric Gs proteins, [22] and PA and PE selectively bind the two-pore domain potassium channel, K2P4.1.…”
Section: Validating the Mass Spectrometry Platformmentioning
confidence: 99%